PHYSICAL FITNESS AND INJURIES: 54 WEEKS OF PHYSICAL TRAINING AMONG MILITARY POLICE OFFICERS - Muniz de Araujo, Lia Grego [UNESP]; Sanches, Marcelo; Turi, Bruna Camilo [UNESP]; Monteiro, Henrique Luiz [UNESP] (Soc Brasileira Med Esporte, 2017)
Introduction: Physical fitness is imperative for military police officers. However, although the purpose of military training is to improve different components of physical fitness, its inadequate performance may be associated with the development of musculoskeletal injuries. Objective: To verify the effect of military physical training on indicators of physical fitness and incidence of musculoskeletal injuries in participants of the Training Course of Military Police Officers in the State of Sao Paulo. Methods: The sample consisted of 86 men who were submitted to the Physical Fitness Test at the beginning and after 54 weeks of training. Information on injuries was obtained with a specific questionnaire. Results: There was significant improvement in maximum oxygen uptake (VO2max), localized muscle endurance, strength and velocity at the end of training. However, 45.3% of the officers suffered one or more injuries, 65.6% of which were concentrated in the lower limbs, 18% in the upper limbs, and 16.4% in the torso and head. The osteoarticular level concentrated 50.8% of the injuries, the musculoligamentous level, 26.3%, and the tegumentary level, 22.9%. Conclusion: Despite the satisfactory results regarding physical fitness, the incidence of injuries among military police officers was high.
Keywords: physical fitness; military personnel; musculoskeletal system/injuries